Well-being, social and economic value of aquatic and leisure centres: a holistic model. Issue 2 (15th March 2022) - Stanway, Alicia R.; Powell, R.; Fradd, L.; Sibson, R.
ABSTRACT: Aquatic and leisure centres (ALCs) are important community spaces that contribute to the health and well-being of users, and to the economy, yet the actual value of the facilities and services provided is difficult to measure. In order to quantify the value of ALCs, the authors developed a well-being (reduced risk of chronic disease, mental illness and drowning, and improved productivity), social (educational uplift and volunteer hours supported) and economic (Gross Value Add and employment) value model. Using a sample of Western Australian ALCs, the well-being and social value component of the model indicates that, on average, an ALC provides $1.79m in overall well-being and social value; while from an economic perspective, generates $1.03m in direct GVA and 34 direct jobs. As key players in planning for healthier and happier communities, the current model empowers ALC practitioners to articulate the holistic value of an individual ALC.